(untitled) (Journal of Educational Sciences, 2020)
The article is of an overview nature, the researchers describe the features of pedagogical communication, the goals of pedagogical communication, as well as the functions of communication, types of information in communication, etc. The authors reveal paralinguistic and extralinguistic systems of signs in pedagogical communication, proxemics as directions of nonverbal means of communication. The purpose of the article is to reveal the features of pedagogical communication, content, functions, types of communication, etc.; to justify the acmeological approach in solving the problems of developing the teacher’s professionalism, improving communication styles and communication strategies of the pedagogue. As results, the authors reveal some of the problems in communication. Moreover, they emphasize that acmeological design is used for individual work related to the strategy of life, the definition of improving behavior or professional communication. Acmeological counseling is an aid to pedagogues in reaching the top of their professional services. Acmeology helps to identify factors, conditions, mechanisms determining the success of self-improvement and relationship self-identity to professional occupation, in general, in life. In acmeological understanding, the main content of development should be advanced progressive and humanistic development (not other, especially egoistic), problems of selfimprovement and self-education of the individual. Key words: acmeology, pedagogical communication, competence, teacher, pedagogue development, professional development of pedagogues.